A qualitative exploration of traditional medicine use in maternal health: experiences of healthcare providers in selected health care facilities in Zambia - Zulu, Wanga; Mumba Zulu, Joseph; Michelo, Charles; Jacobs, Choolwe (International Journal Of Community Medicine And Public Health, 2025)
Background: Traditional medicine (TM) remains widely used by women in Zambia, especially during pregnancy and childbirth. Over the past years, researchers have tried to address the safe integration of TM in maternal health. Use of traditional medicine remains a dilemma to the Health Care Workers (HCWs) who have limited or no knowledge on the effects. This study explored the experiences of healthcare workers regarding use of traditional medicine among women during maternal healthcare. Methods: A phenomenological design was conducted in Lusaka, Solwezi and Kaoma districts of Zambia between November 2020 and February 2021. In-depth interview (IDI) guide was used to collect data. A total of 80 HCWs participated in the study, of which majority (n=62) were Front line HCWs working in the Maternal health units and the remainder were Policy makers and programme coordinators serving at district, provincial and national level (n=18). Thematic analysis was used to identify key themes. Results: HCWs reported mixed experiences. While some acknowledged the cultural significance of traditional practices, many raised concerns about their harmful effects, particularly during labor and delivery. Conclusions: The study was observed a multifaceted mixture of cultural, personal and systemic constraints regarding use of traditional medicines in general. These findings confirm presence of a complex, tension-filled terrain shaped by systemic gaps, cultural beliefs and professional vulnerabilities spread across rural urban contexts in this population.